Service quality in general insurance industry - Jamal, Ahmad Zawawi (2012)
The main purpose of this study is to investigate service quality of the general insurance industry using the service performance gap model. Under the service performance gap model a service performance gap is defined as the discrepancy between service performance expectations of customers and actual service delivered (A Parasuraman,Valeria A. Ziethaml, Leonard L. Berry, 1988). An ANOVA and Independent Sample T-Test were deployed to explore on the variables data. Factor Analysis using Principal Component Analysis approach had been deployed in looking for the "clumps" among the inter correlations of a set of variables. Result had indicated that even though the gap between the perception and expectation was nominal, continuous effort need to be taken by the insurance company in order to increase the level of satisfaction. Assurance is known to be the priority in the service dimensions irrespective of the general insurance agents' demographic. Empathy dimension however is not a priority in this study.